1991
DOI: 10.1055/s-2006-960018
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation Inhibitors from the Seeds ofSwietenia mahagoni: Inhibition ofin vitroandin vivoPlatelet-Activating Factor-Induced Effects of Tetranortriterpenoids Related to Swietenine and Swietenolide

Abstract: The ether extract from the seeds of Swietenia mahagoni Jacq. (Meliaceae) was found to inhibit platelet-activating factor (PAF)-induced platelet aggregation. Systematic separation of the extract afforded twenty eight tetranortriterpenoids related to swietenine and swietenolide. Among them, several new compounds, named swietemahonin A, D, E, and G and 3-O-acetylswietenolide and 6-O-acetylswietenolide, showed a strong inhibition against PAF-induced aggregation in vitro and in vivo assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Among them, several new compounds, named swietemahonins A, D, E, and G and 3-O-acetyl-swietenolide and 6-O-acetyl-swietenolide were identified. These compounds have been shown to strongly inhibit plateletactivating factor (PAF)-induced platelet aggregation [16] . In the seeds, two tetranotriterpenoids, mahonin ( Figure 4) and secomahoganin ( Figure 5), were isolated.…”
Section: Constituent Phytochemicalsmentioning
confidence: 99%
“…Among them, several new compounds, named swietemahonins A, D, E, and G and 3-O-acetyl-swietenolide and 6-O-acetyl-swietenolide were identified. These compounds have been shown to strongly inhibit plateletactivating factor (PAF)-induced platelet aggregation [16] . In the seeds, two tetranotriterpenoids, mahonin ( Figure 4) and secomahoganin ( Figure 5), were isolated.…”
Section: Constituent Phytochemicalsmentioning
confidence: 99%
“…Ekimoto et al (1991) showed that several tetranotriterpenoids, isolated from Swietenia mahogany L. Jacq. (Meliaceae), strongly inhibited PAFinduced aggregation, while glycyrrhizin, an anti-inflammatory compound from Glycyrrhiza glabra Linne, has been identified as a new thrombin inhibitor (Franscichetti et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The platelet aggregation test described by Ekimoto et al (1991) was modified and performed with collagen (500 µg/mL) and ADP (0.05 µm) was used as an aggregation agent. A 0.2 mL aliquot of PRP to which was added a 10 µL aliquot of a test solution was placed in a test tube and stirred at 1200 rpm, at 37°C, for 1 min.…”
Section: Anti-endotoxin-induced Dic Effect In Normal Ratsmentioning
confidence: 99%